The relevance of Mini Mental State Examination (MMSE) use on demential interdiction exams in judicial proceedings - Débora Mascella Krieger; Luiz Carlos Illafont Coronel; Liliane Dias de Lima (Jornal Brasileiro de Psiquiatria, 2020)
ABSTRACT Objective To highlight the important role of Mini Mental State Examination (MMSE) use on judicial interdiction assessments. Methods On this paper, we present a case in which we have used the Mini mental state examination (MMSE) for screening an initial dementia diagnosis, suggested by clinical and mental state examination. Results The relevance of using a screening test for demencial states on judicial interdictions assessments, as MMSE, in order to provide more objective findings to the court, has been demonstrated. Also, we review the current evidence for using MMSE on this setting and the importance of its use on demential interdiction exams in judicial proceedings. Conclusions Judicial evidence is a critical element in decision making. Judicial interdiction assessment is usually performed by expert psychiatrists. As psychiatric diagnosis relies on clinical history and mental state examination, it is composed of subjective elements, varying also according to the examiner’s personal technical orientation and impressions. Neuroimaging exams are helpful on a minority of cases, in which specific findings are present. In such cases, clinical screening questionnaires play an important role - providing objective elements of neuropsychic functioning of an individual, thus limiting the subjective realm of the expert forensic report.